Quantitative Stellar Classification with Low-Resolution Spectroscopy. Issue Volume 8:Issue S293(2012) (29th April 2014) - Eiff, Matthias Ammler-von; Sebastian, Daniel; Guenther, Eike W.
Abstract: Low-resolution spectroscopy (R ≈ 1000) is used to efficiently characterize faint stars suspected to host planets. Stellar parameters, i.e. effective temperature, surface gravity, and metallicity can be assessed from these spectra by methods of quantitative classification. For this purpose, more than 130 template stars have been observed with the faint object spectrograph at the Tautenburg 2m telescope, Germany. A large number of lines are measured and the dependence of line depths on stellar parameters is studied.